Improving the effectiveness of software development projects through a hybrid approach: An analysis of results and impacts (Research, Society and Development, 2023)
The aim of this article is to analyze the adoption of hybrid approaches that combine elements of agile and traditional methodologies to maximize the chances of success of software development projects. The research used the hypothetical-deductive methodology based on bibliographic reviews. Both methodologies have unique characteristics that can better suit a given project. However, the obstacles in reconciling agile and traditional methodologies are based on the difficulties that each methodology proposes in relation to the other. Therefore, it is essential to consider the particularities of each methodology and evaluate its applicability in relation to the needs and requirements of the project in question. The hybrid model is an ideal option because it combines the best of both methodologies.